The Cultural Determinants of FDI Inflows in Tourism: Global Evidence - Doytch, Nadia (Archīum Ateneo, 2023)
This study analyses the determinants of foreign direct investment (FDI inflows in tourism with an emphasis on the cultural determinants for a global sample of countries. More specifically, we examine the role of the presence of UNESCO heritage sites as a factor of tourism FDI. The results show that the recognition of UNESCO heritage sites, along with domestic tourism demand are leading factors of tourism FDI. In addition, we document some interesting findings regarding the traditional determinants of tourism FDI. Economic growth, trade openness, and depreciation of the domestic currency are found to have a positive impact, while labor force participation rate, and agricultural share in total output have a negative impact. The study also documents detailed effects of various aspects of institutional quality on tourism FDI. We find a rich set of results, including a positive impact by better government stability, voice, and accountability, and low risk of external conflict, and mixed effects by the other aspects of institutional quality. The results imply that FDI inflows in tourism reflect both common FDI features and tourism-specific FDI motivations.